Hypoxia, oxidative stress, and immune evasion: a trinity of the trichothecenes T-2 toxin and deoxynivalenol (DON) - You, Li; Zhao, Yingying; Kuca, Kamil; Wang, Xu; Oleksak, Patrik; Chrienova, Zofia; Nepovimova, Eugenie; Jaćević, Vesna; Wu, Qinghua; Wu, Wenda (Archives of toxicology, 2021)
T-2 toxin and deoxynivalenol (DON) are type A and B trichothecenes, respectively. They widely occur as pollutants in food and crops and cause a series of toxicities, including immunotoxicity, hepatotoxicity, and neurotoxicity. Oxidative stress is the primary mechanistic basis of these toxic effects. Increasing amounts of evidence have shown that mitochondria are significant targets of apoptosis caused by T-2 toxin- and DON-induced oxidative stress via regulation of Bax/B-cell lymphoma-2 and caspase-3/caspase-9 signaling. DNA methylation and autophagy are involved in oxidative stress related to apoptosis, and hypoxia and immune evasion are related to oxidative stress in this context. Hypoxia induces oxidative stress by stimulating mitochondrial reactive oxygen species production and regulates the expression of cytokines, such as interleukin-1β and tumor necrosis factor-α. Programmed cell death-ligand 1 is upregulated by these cytokines and by hypoxia-inducible factor-1, which allows it to bind to programmed cell death-1 to enable escape of immune cell surveillance and achievement of immune evasion. This review concentrates on novel findings regarding the oxidative stress mechanisms of the trichothecenes T-2 toxin and DON. Importantly, we discuss the new evidence regarding the connection of hypoxia and immune evasion with oxidative stress in this context. Finally, the trinity of hypoxia, oxidative stress and immune evasion is highlighted. This work will be conducive to an improved understanding of the oxidative stress caused by trichothecene mycotoxins.
Keywords: Animals; apoptóza; Hypoxia; Immune Evasion; oxidační stres; Mitochondria; Deoxynivalenol; Apoptosis; Immune evasion; T-2 Toxin; Oxidative Stress; T-2 toxin; lidé; Reactive Oxygen Species; mitochondrie; hypoxie; Trichothecenes; Oxidative stress; imunitní únik; trichotheceny; reaktivní formy kyslíku; zvířata; Humans